RECOVERY OF RESIDUAL OIL FROM PALM OIL MILL EFFLUENT USING POLYPROPYLENE NANOFIBER: A FIELD TRIAL - Chung, Chin; Janaun, Jidon; Semilin, Veroneka; Balan, Winnie (MATTER: International Journal of Science and Technology, 2017)
Palm oil mill effluent (POME) is an inevitable by-product of palm oil industry that challenges the engineering solutions for its complexity and recalcitrance in nature. This paper reports a new approach to solve the POME pollution, through the recovery of residual oil as opposed to the elimination approach. A field trial of this approach was successfully carried out in a local palm oil mill in Sandakan, Sabah, Malaysia. The recovery of oil was done using novel polypropylene nanofiber (NF) placed in a sludge pit before the treatment pond. NF was packed in flat sheets of wire mesh and bulk bundles, submerged in the POME stream with 5, 6, 7, 15 hours contact times. Saturated NF was removed from pit and oil was desorbed by manual roller press. It recovered 12.19 g of oil/ g NF in 33.75 hours cycle. The recovered oil contained 77% oil content and FFA of 25.05. GC-FID study of the recovered oil indicated no trace of polypropylene contamination. The NF exhibited oil recovery efficiency of 0.06% using 6.7kg of NF. The efficiency is expected to be significantly enhanced if the POME-NF contact is improved as well as the pressing technique. It can fundamentally change the landscape of POME treatment into sustainable, profitable and economical one.